Influence of Gallic Acid-Containing Mouth Spray on Dental Health and Oral Microbiota of Healthy Cats—A Pilot Study - Chaiyavat Chaiyasut; Bhagavathi Sundaram Sivamaruthi; Muruganantham Bharathi; Chawin Tansrisook; Sartjin Peerajan; Khontaros Chaiyasut; Suchanat Khongtan; Kittidaj Tanongpitchayes; Nichaphat Thongma; Natcha Chawnan; Kriangkrai Thongkorn (Veterinary Sciences, 2022)
This pilot study aimed to investigate the effects of gallic acid-containing mouth spray on oral microbiota in healthy cat subjects. Forty healthy cats were recruited and randomly allocated to the control (G1; n = 20) and treatment groups (G2; n = 20). The cats were treated with mouth spray twice daily for 42 days. The changes in the gingival index (GI) and plaque index (PI) were measured at baseline (day 0) and end of the study (42nd day). The changes in the oral microbial composition of representative animals (control, n = 9; and treatment, n = 8) were also evaluated at baseline and end of the study. Oral microbial composition was assessed by amplifying the V1–V3 region of the 16S rRNA gene from supragingival dental plaque DNA extracts. The sequences were annotated using the QIIME 2.0. The GI and PI were significantly reduced after 42 days of treatment. The deep sequencing revealed that mouth spray influenced the cats’ oral microbiome and was significantly diverse. About 20 phyla and 59 species were observed after 42 days of mouth spray usage in cats’ oral microbiota. The number of operational taxonomic units (OTUs) of post-treatment samples (PoTS) of G2 was greatly reduced compared to other samples. Further analysis revealed that mouth spray acts substantially against Desulfomicrobium orale, one of the known pathogens in periodontal disease. The mouth spray efficiently reduced the growth of 22 species and uprooted 17 species. Moreover, the mouth spray supported the growth of normal oral microbiota, including Moraxella and Neisseria species. The preliminary study suggested that the gallic acids-containing mouth spray could be an essential oral product to improve the oral hygiene of the cats. Moreover, further studies are needed to confirm the beneficial effect of mouth spray on cats.